Ultrasonic propagation for measuring the activation energy and volume of a hole in liquids - Ali, M.G. S.; Ebeid, M. R.; Mohamed, Esam A. (Archives of Acoustics, 2002)
Mathematical expressions are introduced in this paper in order to measure the compressional relaxation time by the propagation of ultrasonic waves in associated and nonassociated liquids. The expressions are based on the concept of complex and frequency-dependent compressibility represented as a function of ultrasonic velocity and absorption in liquids. The available experimental data reported earlier in the literature are used in these mathematical expressions to calculate the molecular activation energy and the volume of a hole for some liquids. The introduced expressions concern the relations between the liquid compressional relaxation time and Frenkel's intermolecular relaxation time at different values of temperature and pressure. The effect of vibrational relaxation, bulk viscosity and structural rearrangement on ultrasonic absorption in liquids has been investigated.